India as Growth Pole in South Asia - Ishaq, Maryam; Munir, Farzana; Bashir, Furrukh (Pakistan Journal of Humanities and Social Sciences, 2023)
This paper aims at assessing the spill over effects of Indian economic growth on its regional neighbours, the short run and long run co-movements of Indian GDP, food inflation and overall inflation against the corresponding macroeconomic fundamentals of its regional trading partners are explored. The short- and long-run association between the models variables is investigated by employing modern time-series econometric estimators including Impulse Response Functions (IRFs) and Autoregressive Distributed Lag (ARDL) approach to Cointegration. The results reveal that during short run, South Asian (SA) macroeconomic variables respond significantly towards Indian variables in the event of Indian economy receiving positive exogenous shocks. There is relatively weak evidence in favor of Indian growth spill overs when we test the hypothesis country-by-country, through ARDL model. This lack of support is more visible when SA exports are regressed on Indian GDP. However, for two cases of inflation, one obtains reasonable amount of support. On contrary, the long-run association amongst SA exports and Indian GDP established through two Panel cointegration tests, there is strong support in favor of proposed hypothesis, emphasizing the fact that Indian economic growth bears strong spill over effects in short- as well as in long-run towards its regional trading partners.